2023
DOI: 10.3390/curroncol30020109
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatrix Carcinoma: Report of Two Cases of the Head and Review of the Literature

Abstract: Background: Pilomatrix carcinoma (PC) is a rare skin tumor arising from hair follicle matrix cells. It is locally aggressive with a high rate of local recurrence after surgical excision. Few cases in the literature have been described and the management is not well defined. Objectives: The aim of this study was to present two cases of PC located on the head and review the relevant literature about epidemiology, clinical and dermoscopic evaluation, characteristics of local and distant metastases, local recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Despite the prompt neurosurgery and radiotherapy, the patient' final outcome was fatal. Similarly, in their study Toffoli et al 14 found that distant metastases were uncommon, occurring in 10%-13% of patients, of which two (4%) had metastases at the first tumor staging following primary tumor excision, and six (12%) had metastases during follow-up. Most common sites were lung and regional lymph nodes, followed by local bone infiltration, skull bones, brain, and parotid gland.…”
Section: F I G U R E 3 Photographs Of the Patient Intraoperatively De...mentioning
confidence: 77%
See 1 more Smart Citation
“…Despite the prompt neurosurgery and radiotherapy, the patient' final outcome was fatal. Similarly, in their study Toffoli et al 14 found that distant metastases were uncommon, occurring in 10%-13% of patients, of which two (4%) had metastases at the first tumor staging following primary tumor excision, and six (12%) had metastases during follow-up. Most common sites were lung and regional lymph nodes, followed by local bone infiltration, skull bones, brain, and parotid gland.…”
Section: F I G U R E 3 Photographs Of the Patient Intraoperatively De...mentioning
confidence: 77%
“…Most common sites were lung and regional lymph nodes, followed by local bone infiltration, skull bones, brain, and parotid gland. Only one patient had diffuse metastases to the lung, pleura, liver, and bones 14 . The role of chemotherapy is still debated 9,12 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 Rates of metastasis are reported to be as high as 17%. 4 The challenge is further compounded by resistance to chemotherapy. 5 The case herein demonstrated a rapid in-field progression of metastatic pilomatrix carcinoma during radiation, reflecting the aggressive nature of this cutaneous malignancy and perhaps suggesting a component of radioresistance to even high doses of radiation delivered with SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Pilomatrix carcinoma (PC) is an extremely rare, locally aggressive, malignant skin tumor arising from aberrant proliferation of the hair follicles matrix [ 1 ]. PC arises de novo or through malignant transformation of a pre-existing pilomatrixoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…PC arises de novo or through malignant transformation of a pre-existing pilomatrixoma [ 2 ]. It most predominantly affects male with a male-to-female ratio of 1.3:1 and demonstrates a bimodal age distribution [ 1 , 2 ]. PC mostly arises in the head and neck, and usually presents as a nodular, violaceous, firm, painless lesion that grows rapidly with overlying ulceration [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%